2015
DOI: 10.1001/jamapediatrics.2015.0269
|View full text |Cite
|
Sign up to set email alerts
|

Association of Parental Adverse Childhood Experiences and Current Child Adversity

Abstract: sity as well as the effect of parental ACE on factors contributing to child resilience, such as parenting style and attachment. If these associations prove to be predictive, screening for parental ACE in pediatric practice would allow for early intervention to increase family resiliency and minimize risk for current child adversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 5 publications
2
30
0
Order By: Relevance
“…These findings are consistent with those of Randell et al. () and suggest caregiver ACEs are related to a child's current risk for adversity. Assessment of caregiver ACEs and current adversities would definitely add time to pediatric health care encounters.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with those of Randell et al. () and suggest caregiver ACEs are related to a child's current risk for adversity. Assessment of caregiver ACEs and current adversities would definitely add time to pediatric health care encounters.…”
Section: Discussionsupporting
confidence: 91%
“…A substantial body of literature corroborates the findings of the original ACE study, supporting prevention of early life adversity as a means to improve lifelong health (Garner et al., 2012; Luby, ; Shonkoff et al., ). A more limited body of research indicates that caregiver ACEs may also result in increased risk to children, perpetuating generational cycles of adversity and poor health (Randell, O'Malley, & Dowd, ). Exploring the experiences and risks of children being raised by adults with high ACEs presents a new paradigm for pediatric health care providers.…”
Section: Introductionmentioning
confidence: 99%
“…Our study also showed that children having lived with parents having experienced four or more adverse childhood experiences had a 0.87% (7.2 mmol/mol) higher HbA1c when compared to children of parents who had exposure to less than four adverse childhood experiences. Randell et al, in their study on 215 parents and their children, reported that those children who lived with parents with exposure to four or more adverse childhood experiences, were at higher risk of being exposed to childhood adversities [5]. Parents who had experienced significant stress may find it challenging to provide their children with secure and stable environments to thrive.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse childhood experiences (ACEs) are stressful or traumatic events that have been linked to the development of a variety of health problems, such as obesity, depression and anxiety. In a study by Randell et al, parental adverse childhood experiences also correlated positively with child adversity [5]. Parental psychological stress has been shown to be a predicator of metabolic control in children with type 1 diabetes [6].…”
Section: Introductionmentioning
confidence: 97%
“…50 This may represent a missed opportunity for physicians to improve population health by using a 2-generation approach to simultaneously address health effects of parent ACEs on both parent and child. 51 Although parent ACEs cannot be undone because they already occurred, interventions may promote resilience and mitigate any impact of parents' past experiences on their own and their children's well-being. 52 -54…”
Section: Discussionmentioning
confidence: 99%